PROSEDUR PENGELUARAN KAS SEBAGAI PERTANGGUNGJAWABAN ATAS LAPORAN KEUANGAN - Samhati Hasan (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study will provide a more relevant and what should be used in a better procedure to procedure Cash Expenditure Responsibility to the Financial Statements as at MTsN 1 Bojonegoro.Jenis this research is descriptive research that aims to accurately describe the properties of an individual , state symptoms or certain groups or to determine the frequency or distribution of a symptom or adjustments are a particular relationship between a symptom with other symptoms in the community. Things to know in relation to this population is the procedure Spending Cash in 1 Bojonegoro MTsN in 2011. In this research the author only uses population just because the population here has included the sample. The method used is a case study (case study) where collection of data by taking some elements which are then investigated in depth and conclusions drawn, while the data collection is done by the method of observation, documentation and interviews. The data analysis in this study is described through a qualitative analysis by describing the facts that occurred a general nature and possible problems encountered and solusinya.Hasil obtained from this research in the form of cash disbursements procedures here yet there are functions and responsibilities between the management of cash with recording function cash.